Understanding the Fear of Street Gangs: The Importance of Community Conditions (Santa Ana, California, 1997) - Lane, Jodi ([Verlag nicht ermittelbar], 2012)
This study was designed as an exploratory study to understand fear of gang crime among residents living in an urban area plagued by gangs. During the Summer of 1997, six focus groups were conducted in Santa Ana, California -- two in lower income neighborhoods, two in middle income neighborhoods, and two in upper income neighborhoods. After the focus groups ended, participants were asked to take disposable cameras with them and take pictures of examples of neighborhood factors that prompted them to fear gangs and then mail them back to me in a postage-paid envelope. The research questions guiding this study were: How do the fear-of-crime perspectives apply to fear of gang crime specifically? When worrying about gang crime, do different people focus primarily on different problems (e.g., some diversity or some disorder), or do the same people think about all of these factors? Findings first showed that all four theoretical perspectives on fear of crime applied to the same people at once, rather than to different people (e.g., some being worried about racial and ethnic differences but others about disorder). Second, findings illustrated specifically how these residents connected the factors into one thought process leading to fear of gangs. Residents in these groups clearly believed that ethnic and cultural diversity, or in this case, recent "illegal" Latino immigrants, brought disorder, which in turn caused community decline and brought gangs. This thought process led to personal fear of gang-related victimization. Their beliefs about these causal connections were primarily influenced by their knowledge and observations that gangs in the area were Latino; by direct observation of area diversity disorder, and decline; and by experience living in their changing neighborhoods over time. In addition, beliefs were fueled by indirect victimization, or knowledge gained primarily through acquaintances such as neighbors and community policing officers.